Autowart injection therapy for recalcitrant warts - Srivastava P; Bajaj A (Wolters Kluwer Medknow Publications, 2010)
Background: Warts are caused by various strains of Human Papilloma Virus. They involve the epithelium of the skin and mucus membrane. Various treatment options are available, but extensive and recalcitrant warts not only cause distress to the patient cosmetically and psychologically but also pose a therapeutic challenge to the treating dermatologist. Aim: To evaluate the efficacy of autowart injection as a treatment option for extensive and recalcitrant warts. Materials and Methods: Autowart injection was prepared by removing 3 to 4 mm size wart with radiocautery which was crushed under aseptic condition and injected in the gluteal region by suspending in water for injection. Result: Results were evaluated in 53 available patients who turned up for follow-up; 35 patients (66.03%) had complete resolution in 2 months time, 12 patients (22.64%) showed partial improvement, whereas six patients (11.32%) had no improvement. Conclusion: Autowart injection is suggested as an effective and noninvasive therapeutic option in extensive and recalcitrant warts where most of the available therapies are inconvenient for both patient and treating dermatologist.